2021
DOI: 10.3389/fpsyg.2021.697096
|View full text |Cite
|
Sign up to set email alerts
|

Health Behavior and Associated Factors in Young Adult Cancer Patients

Abstract: Objectives: Having cancer in young adulthood increases the risk of adverse long-term health effects. These risks can be influenced by one’s health behavior (HB). The aim of this study is therefore to investigate the presence of health behavior in adolescents and young adults (AYAs) and to identify associated factors.Design: Young cancer patients (18–39 years old at time of diagnosis) were surveyed at baseline and 12 months later via online or as a paper-pencil version.Methods: A spectrum of indicators for HB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…Barriers to psychosocial health have been reported previously [70] and this has emerged as one of the biggest unmet needs for this population. Previous health-related behavior research suggests a gendered effect-with males being more likely to adopt an avoidant coping style to healthcare consultations and medical advice [71]. However, avoidant behavior was reported by both males and females in our interviews, in relation to support seeking from formal and informal sources.…”
Section: Discussioncontrasting
confidence: 61%
“…Barriers to psychosocial health have been reported previously [70] and this has emerged as one of the biggest unmet needs for this population. Previous health-related behavior research suggests a gendered effect-with males being more likely to adopt an avoidant coping style to healthcare consultations and medical advice [71]. However, avoidant behavior was reported by both males and females in our interviews, in relation to support seeking from formal and informal sources.…”
Section: Discussioncontrasting
confidence: 61%
“…However, perceived stress and anxiety were inversely associated with physical activity in bivariate analyses, indicating that mental health may still be important to address in physical activity interventions for this population. Moreover, identifying as a woman was inversely associated with physical activity in the adjusted models, which is surprising given that women with and without a history of cancer have been reported to engage in more health-conscious behaviors, such as physical activity [ 48 , 49 ]. Physical activity interventions may be particularly important for women cancer survivors in this age group, but further research is needed to understand this finding and the complex relationship between survivorship and physical activity among all YA survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased ADL ability and the presence of psychological distress are physical and mental health problems that manifest with age (11,12). These problems are partly influenced by health behaviors (11,13). Previous studies have shown that health behaviors are a combination of different behavior patterns and that health behaviors such as smoking, drinking and engaging in physical exercise can significantly affect changes in ADL ability and psychological distress (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…These problems are partly influenced by health behaviors (11,13). Previous studies have shown that health behaviors are a combination of different behavior patterns and that health behaviors such as smoking, drinking and engaging in physical exercise can significantly affect changes in ADL ability and psychological distress (12)(13)(14). ADLs refer to the most basic and common activities that people carry out repeatedly every day to maintain survival and adapt to the living environment (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation